2015
DOI: 10.2174/1566524015666150114110551
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Nutritional Interventions and Physical Exercise in Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in adults and its prevalence is rising around the world. This pathology is characterized by accumulation of liver fat, which exceeds 5% of liver weight in absence of alcohol consumption, viral infection or other hepatic etiology. Since NAFLD has been associated with obesity, insulin resistance, diabetes or alteration of lipid profiles, it is considered as the liver manifestation of metabolic syndrome. Pathogenic mechanisms of NAFLD have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 0 publications
0
29
0
6
Order By: Relevance
“… were demonstrated that loosing 5% and 7% of total body weight was associated with improved liver enzymes and histological changes. Recently, it has been suggested that nutritional interventions including low fats and low carbohydrates diets along with higher polyunsaturated fatty acids intake might beneficially influence NAFLD . Bezerra Duarte et al .…”
mentioning
confidence: 99%
“… were demonstrated that loosing 5% and 7% of total body weight was associated with improved liver enzymes and histological changes. Recently, it has been suggested that nutritional interventions including low fats and low carbohydrates diets along with higher polyunsaturated fatty acids intake might beneficially influence NAFLD . Bezerra Duarte et al .…”
mentioning
confidence: 99%
“…Moreover, quality of life is also improved in these patients as a result of weight loss [233]. Further to total ingested calories, saturated fats, carbohydrates, and fructose-rich beverages all need to be restricted and, conversely, increases in MUFA, long-chain PUFA, and caffeine should be promoted [234].…”
Section: Lifestyle Changesmentioning
confidence: 99%
“…Physical activity has been shown to be beneficial in the treatment of insulin resistance and type 2 diabetes (14,25,51,66); therefore, the effect of exercise on ectopic lipids has gained significant interest.…”
mentioning
confidence: 99%